AN ANALYTICAL STUDY OF THE LEVEL OF EMPOWERMENT AMONG TEACHERS OF PHYSICAL EDUCATION IN THE CENTRE OF MAYSAN GOVERNORATE FROM THE POINT OF VIEW OF SPECIALIZED SUPERVISORS (Neo Scientific Peer Reviewed Journal, 2023)
The importance of the study in the extent of Influence of level of empowerment the teachers of physical education in the centre of Maysan governorate, from the point of view of the supervisors, have specialization in the subject of physical education. Where m problem appears Research in the study of the level of empowerment The teachers of physical education in the centre of Maysan governorate, from the point of view of the supervisors, have specialization. The research objectives can be summarized as follows: Building and applying a measure of the level of empowerment for teachers from the point of view of supervisors specializing in the education of Maysan Governorate, as well as setting standard levels for a measure of the level of empowerment for teachers of physical education. The research community consists of Physical education teachers in Maysan Governorate. For the academic year (20 /22-2023), the number is (215) teachers. The sample was chosen by the intentional method, which consisted of (208) teachers representing teachers of physical education in the district of Amarah, the centre of Maysan Governorate, and was distributed among three groups: the reconnaissance research sample, which included (7) teachers, with a rate of 3.36 %, and the building sample, which included (112) teachers, with a rate of 53.84% and the final application sample, which included (96) teachers, with a percentage of 46.15 %. The researcher concluded Building and rationing is a special measure to measure the level of empowerment of physical education teachers. The researcher also concluded that the level of empowerment of physical education teachers is good, and therefore the teachers were at the required level and gave everything they had for the lesson. As for the most important Recommendations, the researcher recommends that the teacher should be given more time to prove its positive impact on the students and on the results of the lesson as a whole, and the need to conduct similar studies to find out the level of empowerment of teachers for the various educational levels.